Analisis Faktor-Faktor Yang Mempengaruhi Minat Siswa Dalam Pemilihan Program Keahlian Akuntansi di SMKN 2 Padang - Sri Ayu Ningsih; Jean Elikal Marna (Universitas Negeri Padang, 2023)
This study aims to analyze the factors that influence students' interest in choosing accounting expertise program. This research is a quantitative descriptive associative research with using simple random sampling technique. The research population was 125 students from SMK N 2 Padang. Data obtained using a questionnaire distributed to 125 students who carry out online learning. The data obtained were processed by descriptive and factor analysis. The results showed that the 4 factors that influence students' interest in choosing accounting skills programs, namely learning motivation, learning methods, parents and school. Based on the results of the study, it is recommended that students be more active in repeating learning, schools further improve teacher-student relations by rewarding success students and support students who are left behind, and for parents to discuss more with children about the chosen major and future prospects.